MATH SOLVE

5 months ago

Q:
# Find the average rate of change for the given function from x = β1 to x = 2.Graph of f of x equals negative three x plus 2

Accepted Solution

A:

[tex]the \: average \: rate \: of \: change = \frac{f(x2) - f(x1)}{x2 - x1} \\ \frac{f(2) - f( - 1)}{ 2 - - 1} = \\ \frac{ - 3(2) + 2 - ( - 3( - 1) + 2)}{3} = \\ \frac{ - 6 + 2 - 3 - 2}{3} = \frac{ - 9}{3} = - 3[/tex]

[tex]the \: average \: rate \: of \: change = \frac{f(x2) - f(x1)}{x2 - x1} \\ \frac{f(2) - f( - 1)}{ 2 - - 1} = \\ \frac{ - 3(2) + 2 - ( - 3( - 1) + 2)}{3} = \\ \frac{ - 6 + 2 - 3 - 2}{3} = \frac{ - 9}{3} = - 3[/tex]